2011
DOI: 10.1002/jmv.21788
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and viral load of hepatitis C virus among persons attending a voluntary counseling and testing center in Ethiopia

Abstract: The prevalence of different genotypes of hepatitis C virus (HCV) in Ethiopia is not known. HCV genotypes influence the response to therapy with alpha-interferon alone or in combination with ribavirin. A cross sectional study was conducted on attendees of voluntary counseling and testing center. Serum samples from 1,954 (734 HIV positive and 1,220 HIV negative) individuals were screened for HCV antibody. Active HCV infection was confirmed by quantitative PCR in 18 of the 71 samples with anti-HCV antibodies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Genotype 4a is the most prevalent genotype 4 HCV strain around the world and transmission was amplified in North Africa, particularly Egypt as a result of unsafe injection practices in healthcare settings (21). Clinical trials have focused on this subtype, and to a lesser extent genotype 4d, a strain introduced to Saudi Arabia during the early 20 th century (22), probably from countries in the Horn of Africa including Ethiopia (23). It has more recently emerged in PWID in Southern Europe and found a sexually-transmitted niche in men-who-have-sex-with-men (MSM) in Northern Europe with cross-over from PWID to MSM likely occurring in urban centres such as Amsterdam, London, Berlin and Paris (24).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype 4a is the most prevalent genotype 4 HCV strain around the world and transmission was amplified in North Africa, particularly Egypt as a result of unsafe injection practices in healthcare settings (21). Clinical trials have focused on this subtype, and to a lesser extent genotype 4d, a strain introduced to Saudi Arabia during the early 20 th century (22), probably from countries in the Horn of Africa including Ethiopia (23). It has more recently emerged in PWID in Southern Europe and found a sexually-transmitted niche in men-who-have-sex-with-men (MSM) in Northern Europe with cross-over from PWID to MSM likely occurring in urban centres such as Amsterdam, London, Berlin and Paris (24).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 21 Clinical trials have focused on this subtype, and to a lesser extent genotype 4d, a strain introduced to Saudi Arabia during the early 20 th century, 22 probably from countries in the Horn of Africa including Ethiopia. 23 It has more recently emerged in PWID in Southern Europe and found a sexually-transmitted niche in men-who-have-sex-with-men (MSM) in Northern Europe with cross-over from PWID to MSM likely occurring in urban centres such as Amsterdam, London, Berlin and Paris. 24 While the globally dispersed genotype 4a and 4d lineages are well described, others prevalent in sub-Saharan Africa have only recently been investigated in clinical studies.…”
Section: Geographical Distribution Of Genotypesmentioning
confidence: 99%
“…The high diversity and predominance of genotype 4 suggests that this genotype has been endemic for a longer time in Ethiopian population. A previous study also showed the dominance of this genotype in Ethiopia [21]. …”
Section: Discussionmentioning
confidence: 74%
“…The only study reporting on HCV genotypes in Ethiopia was limited to few patients attending a voluntary counseling and testing center in Addis Ababa. A total of 18 HCV RNA positive samples were analysed and a dominance of genotype 4 (50%, nine cases) followed by 2 (6 cases), 5 (2 cases) and 1 (1 case) was found [21]. However, no country-wide studies have been published and information on the HCV molecular diversity throughout the country is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of subtype 4d in surveillance studies in West Africa383940 and Central Africa9414243 suggests that this subtype may have emerged along a more eastward trajectory. Although subtype-level data from this region are scarce, the detection of HCV4d in 22% of seropositive samples in a small-scale Ethiopian survey44 supports such a scenario, as do the likely introduction of this subtype in southern Italy by returning colonists, of whom 82% were stationed in the Horn of Africa (Eritrea, Ethiopia and Somalia, the others inhabited Libya)45, and its high prevalence in Saudi Arabia1213.…”
Section: Discussionmentioning
confidence: 94%